Synthesis of Tumbleweed-like MoSe2 Nanostructures for Ultrasensitive Electrochemical Detection of Uric Acid - Peizheng Shi; Ningbin Zhao; Zhuang Sun; Kaiqiang Sun; Wubo Chu; Hsu-Sheng Tsai; Lidong Wu; Tao Cai; Yuezhong Wang; Nan Jiang; Chen Ye; Li Fu; et al. (Chemosensors)
Uric acid (UA), the final metabolic product of purines, plays a crucial role in human health monitoring. The UA concentration in biological fluids serves as a diagnostic marker for various disorders, particularly kidney diseases, and represents a potential therapeutic target. Given the growing emphasis on preventive healthcare, developing methods for real-time UA detection has become increasingly significant. Here, we demonstrate the synthesis of novel tumbleweed-like molybdenum diselenide (MoSe2) nanostructures through a single-step hydrothermal process. The synthesized MoSe2 was subsequently hybridized with reduced graphene oxide (rGO) to construct electrodes for UA sensing. Differential pulse voltammetry (DPV) measurements revealed that the MoSe2/rGO-modified glassy carbon electrode (GCE) exhibited excellent UA detection capabilities under optimized conditions. The sensor demonstrated a remarkably low limit of detection (LOD) of 28.4 nM and maintained linearity across a wide concentration range (40 nM to 200 μM). Notably, the sensor showed high selectivity for UA detection even in the presence of common interfering species, including citric acid (CA), dopamine (DA), ascorbic acid (AA), cysteine (Cys), glucose (Glu), oxalic acid (OA), sodium ions (Na+), and potassium ions (K+). The developed sensor displayed outstanding selectivity, stability, and reproducibility characteristics. This synthetic approach offers promising opportunities for developing MoSe2-based electrochemical sensing platforms suitable for diverse bioanalytical applications.